Development of Interactive Edugame Learning Evaluation Assited by Wordwall to Improve IPAS Learning Outcomes - Avina Prameswari; Aldina Eka Andriani (Jurnal Penelitian Pendidikan IPA, 2024)
Teachers are less than optimal in conducting a variety of technology-based learning evaluations, this is supported by learning evaluations that are still conventional, causing low students learnig outcomes. Purpose of this research is to develop a design, test the feasibility and effectiveness of interactive edugame learning evaluation assisted by wordwall to improve IPAS learning outcomes. Type of research is Research and Development (RnD) using the Borg and Gall model. The subjects of this study were 25 fourth grade students of SDN Harjosari 01. Data collection techniques used tests and non-tests. Technical data analysis using normality test, homogeneity test, t test and N-gain test. The results showed: (1) the design of this interactive edugame learning evaluation uses wordwall and canva applications with  cover, learning objectives, learning flow, and learning evaluation; (2) the feasibility of  learning evaluation is shown from the validation results of media experts, material experts, student responses, and teacher responses with a very feasible category; (3) the effectiveness of learning evaluation is shown from the results of the analysis of pretest and posttest scores. The t-test results obtained a sig value. 0,000> 0,05. N - gain test results 0.43 with moderate criteria. The conclusion of this study is the development of interactive edugame learning evaluation assisted by wordwall successfully developed, very feasible, and effective to improve the learning outcomes of IPAS fourth grade students of SDN Harjosari 01